Exploring Dynamic Motivation in Virtual EFL Classrooms: A Qualitative Case Study in Indonesia - Asis Salurante; Nehru P. Pongsapan; Viktor Siumarlata (FOSTER: Journal of English Language Teaching, 2026)
The proliferation of virtual learning environments in English as a Foreign Language (EFL) education has necessitated a deeper understanding of how these digital contexts shape student motivation, particularly in developing country settings where technology-mediated instruction presents unique challenges and opportunities. This qualitative case study investigates the dynamics of student motivation in synchronous online English learning among ninth grade students at a junior high school in Indonesia. Through in-depth semi-structured interviews with ten students, the study employed thematic analysis within Miles and Huberman's interactive framework to explore the multidimensional factors influencing learner motivation in virtual classrooms. The findings reveal that student motivation in synchronous online learning is not a static trait but a dynamic phenomenon shaped by twelve interconnected factors operating across individual, social, instructional, and environmental levels. Interactive and gamified activities particularly quizzes, breakout room discussions, and polling features generated high engagement, while passive instructional approaches such as extended lectures and excessive reading precipitated rapid disengagement. The teacher emerged as the most influential motivational factor, with instructional clarity, appropriate pacing, positive demeanor, and strategic use of praise significantly enhancing student engagement. Platform features played crucial mediating roles, with the chat function effectively reducing speaking anxiety by enabling text-based participation. Peer presence exerted bidirectional influence, as active classmates modeled engagement while collective silence diminished individual motivation. Technical challenges related to internet connectivity and home environment distractions posed significant barriers, yet students demonstrated resilience through adaptive coping strategies. The study contributes theoretical insights into the contextual nature of L2 motivation in digital environments and offers practical implications for educators, curriculum designers, and policymakers seeking to optimize student engagement in virtual EFL classrooms.